The role of Organizational Citizenship Behavior and Quality of Work Life on Employee Performance in the Society 5.0 Era - Sitti Aisyah; Amiruddin Husain; Usman Hamid; Masruhi Kamidin; Muh. Haerdiansyah Syahnur (IECON: International Economics and Business Conference, 2024)
The rapid development of technology, particularly artificial intelligence (AI), in the Society 5.0 era has significantly transformed how organizations operate and interact with employees. This era emphasizes the importance of collaboration between humans and technology to achieve organizational goals more efficiently. In this context, Organizational Citizenship Behavior (OCB) and Quality of Work Life (QWL) are two key factors that influence employee performance. OCB refers to voluntary behaviors that support the organization beyond formal job requirements, while QWL relates to working conditions that promote employee well-being and engagement. This study aims to analyze the impact of OCB and QWL on employee performance at the Department of Cooperatives, SMEs, Trade, and Industry in Pangkep Regency, which has implemented OCB principles through routine activities such as community service, retirement celebrations, and quarterly meetings. This is a quantitative study using a descriptive and explanatory approach. The sample consists of 84 employees selected through purposive sampling. The results show that both OCB and QWL have a positive and significant impact on employee performance. Improvements in OCB and QWL were found to enhance employee performance, both in terms of productivity and interpersonal relationships at the workplace. These findings indicate that a work environment supporting OCB and QWL can create a more productive and harmonious atmosphere, which contributes to the achievement of organizational goals. Furthermore, the study highlights the importance of implementing OCB and QWL, especially in the Society 5.0 era, which is characterized by technological advancements such as AI. By leveraging OCB and QWL, organizations can create a more adaptive environment and improve employee performance, thereby supporting future organizational success.